A Critical Genre Analysis of Broadcast Disaster News - Mohamad Arif Ismail (Merwinspy Publisher, 2026)
This study investigates how broadcast disaster news is constructed and realised as a professional genre within a time-sensitive context. Drawing on Critical Genre Analysis, the study examines the interaction between textual organisation, intertextuality, interdiscursivity, institutional constraints, and professional practice in disaster reporting. The data consist of 23 broadcast disaster news reports from TVRI Central Sulawesi, a regional station of the Indonesian public broadcasting service, supported by an institutional guidebook and interviews with a journalist and an editor. The analysis reveals that disaster news is organised through relatively stable textual conventions while incorporating multiple institutional and discursive voices through the systematic use of external sources. The findings further indicate that professional practice mediates these conventions, as journalists adapt institutional guidelines to meet the demands of immediacy. In addition, the analysis suggests that disaster news is not fully realised within a single report but unfolds across a sequence of interconnected texts over time. The study contributes to Critical Genre Analysis by highlighting the importance of the temporal dimension of genre realisation in time-sensitive professional contexts, suggesting that professional genres may be understood as evolving communicative processes rather than static textual products.